The Implementation and Effectiveness of Recovery Methods in a cohort of South African semi-professional Football Players during pre-season Training: A Case Study - Tevin Blignaut; Cheryl-Ann Volkwyn; Adrian Lombard; Andrew Green (Journal Coaching Education Sports, 2024)
This case study aimed to assess the efficacy of various training methods during the pre-season training of semi-professional football players. The demanding nature of football training places significant strain on players' psychophysiological practices, leading to fatigue. To mitigate fatigue and prevent overtraining, monitoring tools for training loads and recovery interventions are essential. A descriptive cohort case study design, using questionnaires for data collection, applied to 23 football players. The players were observed and evaluated to determine the most preferred recovery methods and monitor psychophysiological fatigue using the well-being questionnaire and Borg's category ratio scale (CR-10) during pre-season training. Recovery interventions tested included active recovery, cold water immersion, and stretching. Analysis revealed that players' well-being consistently fell below baseline levels (p<0.05) according to the well-being questionnaire. Additionally, the CR-10 indicated high perceived training loads among players, with no significant difference observed between the highest and lowest perceived loads (p > 0.05). The effectiveness of the recovery interventions appeared limited, as baseline wellness scores were not achieved. Nonetheless, the high acute training loads experienced during pre-season training may serve as a stimulus for adaptations. Semi-professional players may benefit from tailored combinations of recovery methods following training sessions or games.